2014
DOI: 10.1186/1756-0500-7-531
|View full text |Cite
|
Sign up to set email alerts
|

Poor adherence to the World Health Organization guidelines of treatment of severe pneumonia in children at Khartoum, Sudan

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is as a major cause for childhood morbidity and mortality worldwide. This study was conducted to investigate the adherence and response of the WHO guidelines for treatment of severe pneumonia.MethodA cross-sectional study was conducted in the period of June 2009 to July 2010 at Khartoum Hospital, Sudan. Children admitted and treated for severe pneumonia were enrolled.ResultsOnly 39 (18.8%) out of 208 enrolled children received prescriptions that were adherent to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Condition assessment and diagnosis. A detailed inquiry of the medical history was carried out to determine whether the children patients had a history of recurrent respiratory tract infection, and whether they had measles, whooping cough and other respiratory diseases prior to onset, as well as whether the children patients had a full-term birth or asphyxia, and if the growth and development of children patients after birth was normal (16)(17)(18). Conditions such as fever, cough, extent of choked asthma, the presence or absence of breathing, faster heart rate, pulmonary rales, orthopnea, nose flap, three depression signs and cyanosis, as well as clinical manifestations of infected circulatory, digestive, and nervous system were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Condition assessment and diagnosis. A detailed inquiry of the medical history was carried out to determine whether the children patients had a history of recurrent respiratory tract infection, and whether they had measles, whooping cough and other respiratory diseases prior to onset, as well as whether the children patients had a full-term birth or asphyxia, and if the growth and development of children patients after birth was normal (16)(17)(18). Conditions such as fever, cough, extent of choked asthma, the presence or absence of breathing, faster heart rate, pulmonary rales, orthopnea, nose flap, three depression signs and cyanosis, as well as clinical manifestations of infected circulatory, digestive, and nervous system were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…General information. Ten cases of children diagnosed with severe pneumonia according to the guidelines of the World Health Organization were included in the present study (16). In this group, there were 6 males and 4 females, aged 1 month to 6 years.…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 200 studies were screened for full-text review and, 34 articles with (n = 87,984 patients) were selected for the prevalence and/ or associated factors analysis ( Fig.1). Table 1 summarizes the characteristics of the 34 included studies in the systematic review and metaanalysis [10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. 16 studies were found in Ethiopia [10,[22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Study Selectionmentioning
confidence: 99%
“…Cephalosporins were often reported to be the class with higher rates of prescription for CAP treatment, as reported by many centres in different countries, like Ethiopia [ 60 ], Saudi Arabia [ 62 ], Nepal [ 73 ], Serbia [ 83 ], Sudan [ 67 ], US [ 54 , 71 , 74 ], Italy [ 76 ], and other European countries [ 48 , 82 ].…”
Section: Resultsmentioning
confidence: 99%